The Comparison of Two Method Effectiveness on Postmenopausal Hot Flash Therapy: Acupuncture versus Hormone Therapy: - Mohammadyari, Fatemeh; Seyedmehdi, Sayed Ahmad; Mousavi, Fatemeh; Tabatabaei, Roozbeh (Galen Medical Journal, 2015)
Background: Postmenopausal hot flash is a common disease amongst women with high prevalence of 75%. Hormone Replacement Therapy (HRT) is a well-known relief of symptoms which has disadvantages such as side effects and contraindication for certain types of hormone related diseases and breast or Estrogen related cancers. One of the alternatives is acupuncture which is an East Asian and more specifically Chinese method. In this study hormone therapy and acupuncture effectiveness have been compared in postmenopausal hot flash treatment. Materials and Methods: This study is aimed to initially diagnose vasomotor symptoms such as elevated body temperature, palpitation, headache and perspiration. Afterwards, assessment and finally comparing the efficacy of two methods for each symptom treatment have been carried out. In this clinical trial study, 20 climacteric female samples participated. Two study and control groups have been formed and each method efficacy has been evaluated on each of four major vasomotor symptoms. Results: For all postmenopausal vasomotor symptoms, acupuncture and HRT had similar notably high relief of symptoms effectively; namely in hot flash 90% and 85%, in palpitation 65% and 70%, in perspiration 77.77% and 81.25%, and in headache 50% and 81.3%, respectively. Although in all fields except hot flashes, HRT had slightly better success. Conclusion: This survey pointed out that acupuncture is as effective as hormone therapy in relief of symptoms hot flash for postmenopausal women. Further researches are needed to assess the clear side effects of acupuncture method. [GMJ.2015;4(2):83-89]